Construction of Interfaces in Virtual Reality: a systematic review focusing on Ergonomics and User Experience - Lima, Sofia; Catapan, Márcio Fontana; Zeredo, Jun Sasaki (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
Virtual reality (VR) technology has generated significant global interest, leading to ongoing advancements. However, the development of VR interfaces, particularly concerning ergonomics and user experience (UX), remains underexplored. This paper addresses this gap by conducting a systematic literature review to establish guidelines for optimizing VR interfaces. By analyzing existing studies, we aim to develop guidelines that enhance UX and ergonomic considerations in VR, thereby advancing the effectiveness and accessibility of this technology.